Primary Immunodeficiency Diseases: An Update on the Classification from the International Union of Immunological Societies Expert Committee for Primary Immunodeficiency - Al-Herz, Waleed; Bousfiha, Aziz; Casanova, jean-laurent; Chapel, Helen; Conley, Mary Ellen; Cunningham-Rundles, Charlotte; Etzioni, Amos; Fischer, Alain; Franco, Jose L.; Geha, Raif; Hammarstrom, Lennart; Nonoyama, Shigeaki; et al. (Frontiers in Immunology, 2011)
We report the updated classification of primary immunodeficiency diseases, compiled by the ad-hoc Expert Committee of the International Union of Immunological Societies (IUIS). As compared to the previous edition, more than 15 novel disease entities have been added in the updated version. For each disorders, the key clinical and laboratory features are provided. This updated classification is meant to help in the diagnostic approach to patients with these diseases.